A Case of Hepatocellular Carcinoma in a Patient with Idiopathic Forearm Arteriovenous Fistula - Sayuri Takada; Yutaka Yata; Hirotaka Ishizu; Yuma Inoue; Tomoyasu Kuroda; Shigeki Ikeda; Atsushi Jogo; Akira Yamamoto; Hiroshi Higashiyama; Norifumi Kawada (Case Reports in Gastroenterology)
Introduction: We report an exceedingly rare case of hepatocellular carcinoma (HCC) associated with an idiopathic congenital forearm arteriovenous fistula (AVF). Given the absence of previous reports addressing the treatment of HCC in patients with AVF, we evaluate HCC treatment strategies, including the appropriateness of using angiogenesis inhibitors. Case Presentation: A 74-year-old man was admitted for the evaluation of liver tumors. His medical history included a chronic, intractable idiopathic right forearm AVF, for which he had undergone multiple surgical interventions. Abdominal EOB-MRI revealed multiple small focal lesions across both liver lobes during the hepatobiliary phase, indicative of multiple HCC, and liver biopsy confirmed early-stage HCC. Considering the potential presence of additional vascular anomalies similar to the forearm AVF, local hepatic artery chemoembolization was performed. Since there is still insufficient discussion about the systemic administration of angiogenesis inhibitors to patients with vascular abnormalities such as AVF, we discuss the treatment options for HCC with AVF, including its strategies in the progressed HCC stage. Conclusion: As molecularly targeted therapies continue to evolve, recognizing the unique aspects of cases like ours is crucial. Establishing an appropriate treatment strategy for HCC patients with AVF is imperative, highlighting the need for tailored therapeutic approaches based on individual vascular profiles.